2010
DOI: 10.3109/10641960902993079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Revised UPPP Surgery on Ambulatory BP in Sleep Apnea Patients with Hypertension and Oropharyngeal Obstruction

Abstract: This study aimed to investigate the value of the surgery of revised uvulopalatopharyngoplasty (UPPP) on ambulatory blood pressure (BP) in obstructive sleep apnea/hypopnea syndrome (OSAHS) patients with hypertension and oropharyngeal obstruction. A retrospective cohort study was performed in 29 patients with OSAHS and hypertension, who received treatment with revised UPPP surgery. After surgery 1 month, the Apnea-hypopna index (AHI) and body mass index (BMI) significantly decreased (P < 0.05), and mini SpO(2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Although many patients with OSA worldwide have undergone upper airway surgery, studies of health improvements associated with such surgery are rare and have been conducted with small samples. De Paula Soares et al and Yu et al reported that blood pressure fell after surgery, and Li et al found that the improvements of certain lipids were associated with surgical treatments in OSA, which is in agreement with our data. In addition, these metabolic factors combine multiplicatively to increase the CVD risk .…”
Section: Discussionsupporting
confidence: 93%
“…Although many patients with OSA worldwide have undergone upper airway surgery, studies of health improvements associated with such surgery are rare and have been conducted with small samples. De Paula Soares et al and Yu et al reported that blood pressure fell after surgery, and Li et al found that the improvements of certain lipids were associated with surgical treatments in OSA, which is in agreement with our data. In addition, these metabolic factors combine multiplicatively to increase the CVD risk .…”
Section: Discussionsupporting
confidence: 93%
“…Changes in blood pressure following treatment for OSA were studied with the use of continuous positive airway pressure (CPAP) and intraoral appliances . Only one article in English on blood pressure variations in adults following surgical treatment could be found in the PubMed database …”
Section: Introductionmentioning
confidence: 99%
“…5 Only one article in English on blood pressure variations in adults following surgical treatment could be found in the PubMed database. 6 A new technique for pharyngeal surgery was proposed in 2003: lateral pharyngoplasty. 7 By proposing the myotomy of the superior pharyngeal constrictor muscle and the palatopharyngeal muscle to remove the passive constriction of the pharynx and support the lateral pharyngeal wall, this technique resulted in improved clinical and polysomnographic results compared to the classic and widespread uvulopalatopharyngoplasty (UPPP).…”
Section: Introductionmentioning
confidence: 99%
“…The most common procedure is the revised uvulopalatopharyngoplasty, for which a small study showed improvement in nighttime but not daytime blood pressure [61]. Oral appliances to maintain airway patency have also been used with some success [62].…”
Section: Diagnosis Of Sleep Apnea and Management Of Resistant Hypertementioning
confidence: 99%